Implementasi E-PR dalam Kegiatan Kehumasan Universitas Abdurrab - Nurul Mustaqimmah; Novi Dini Restia; Hawami (CV Insan Kreasi Media, 2023)
Communication activities in the Information and Communication Technology are progressing very rapidly and the use of the internet is increasing every year. Technological advances require public relations to shift from conventional to modern. Many social media developments are increasingly like Facebook, Instagram, WhatsApp, Tiktok and others. Public Relations of Abdurrab University is one that utilizes Digital Public Relations to provide information and increase the value and reputation of the University. The purpose of this study was to determine the extent of the application of Abdurrab University Digital Public Relations in managing the @univrab . Instagram media account. The main theory used in this research is Phillips & Young's Online Public Relations which consists of Transparency, Internet Porosity, Internet as an Agent, Richness in Content and Reach. This study uses a qualitative descriptive method with data collection methods interviews, observation and documentation. The results of this study indicate that Abdurrab University's public relations have implemented Digital Public Relations seen from the context of the @univrab Instagram account in publicly open posts, anticipate accounts, use various kinds of social media and conduct outreach interactions to the public. Digital Public Relations needs to maximize Philips and Young's online theory to broaden the reach of interaction as well as make referrals in finding information.